Institutional dynamics in climate change adaptation – a bibliometric analysis - Jaisridhar, P.; Nirosha, R.; Jasimudeen, S.; Senthilkumar, M.; Ponsneka, I.; Raja, P. (Frontiers in Environmental Science, 2025)
IntroductionClimate change poses significant challenges to agricultural and water sectors globally, threatening food security, water availability, and ecosystem services. Understanding institutional dynamics in climate change adaptation is crucial for developing effective governance responses across different administrative levels.Methods This systematic literature review followed PRISMA guidelines to analyze institutional challenges and enabling factors in climate adaptation governance. A comprehensive search of Scopus and Web of Science databases identified relevant studies published between 2014–2024. After rigorous quality assessment, 38 papers were selected for analysis. Bibliometric analysis was conducted to identify research patterns and geographical distributions.Results The bibliometric analysis revealed research concentration in Western countries and parts of Africa, with significant gaps in South Asian countries. Key institutional barriers identified include governance fragmentation, resource limitations, knowledge gaps, and policy misalignments across sectors and governance levels. Enabling factors that facilitate effective adaptation include boundary organizations, collaborative governance frameworks, and multi-level institutional partnerships. The review identified critical research gaps in understanding informal institutional dynamics, power relations in adaptation governance, and practical implementation pathways for institutional reform.DiscussionThe findings suggest that effective climate adaptation policies in agricultural and water sectors require targeted interventions that balance formal institutional structures with flexible governance approaches. This is particularly important in climate-vulnerable regions where institutional capacity may be limited. The research highlights the need for enhanced understanding of informal governance mechanisms and power dynamics that influence adaptation outcomes, especially in underrepresented regions such as South Asia